Outgassing of TPS pulsed kicker magnets decreased with vacuum firing. (September 2015) - Chan, C.K.; Chang, C.C.; Chen, C.L.; Chen, C.S.; Yang, C.S.
Abstract: Two in-vacuum kicker magnets serve to inject and to extract the electron beams for the TPS injector. A large gas load generated from the outgassing of kicker ferrites (CMD5005) causes concern. To study the effect of vacuum firing in decreasing the outgassing from kicker ferrites, we set up a test bench to record spectra from a residual-gas analyzer (RGA) and measured the rates of outgassing during vacuum firing. The RGA spectrum revealed that water vapor is the dominant gas from the unbaked ferrites; with the throughput method the rate of outgassing, q 2.7 (Ferrite), before baking was 5.5 × 10 −9  mbar L s −1  cm −2 . A duration 40 h of vacuum firing at 200 °C is required to remove the water vapor from the kicker ferrites and to yield a rate between 2.2 × 10 −12 and 2.6 × 10 −12  mbar L s −1  cm −2 after vacuum firing. Highlights: We adopted vacuum firing to mitigate the outgassing of the kicker ferrites (CMD5005). We measured the outgassing rate of the unbaked ferrites q2.7  ∼ 5.5 × 10 −9  mbar L s −1  cm −2 . Vacuum firing at 200 °C with a duration >40 h is required to decrease the amount of water vapor from ferrites. The outgassing rate of the ferrites after vacuum firing can achieve <2.6 × 10 −12  mbar L s −1  cm −2 .